Determining Performance Factors of The Salesman Using Nvivo: Case Study of PT. So Good Food Bandung - Dewi, Meliana Aulia; Gustomo, Aurik (Journal of Business and Management, 2021)
The Food and Beverage industry gives a significant contribution to the national economy. JAPFA is the biggest agriculture food company in Indonesia, while PT. So Good Food Bandung is a local distributor of JAPFA products. This research intends to determine the performance factors of salesman in PT. So Good Food Bandung the case study of unreached sales target by analyzing the current skills development, the caused of salesman low skills, and generate a recommendation to increase skills development. This research used a qualitative approach and Nvivo to generated coding. The result indicates the category of a high performance standard that shows the behavior of Vocal about Career Aspiration, Exude Passion and Positivity, Eager to Develop New Skills, Behave as a Company Ambassador, Aware of Responsibility. Meanwhile, the low performance standard shows the behavior of Lack of New Improvement, Lack of Motivation, Lack of Communication Skills, Constantly Complain, each of the interview participants will generate the score of coding based on that behavior. The finding of this research is expected to give a recommendation for a training program as a tool to increase skills development by considering the result of this research.Keywords: Performance Factors, Salesman, Nvivo, Training Program, Skill Development